PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI PEMBELAJARAN VIRAL ISSUE BASED LEARNING DENGAN METODE FOCUS GROUP DISCUSSION - Anna Suryaningsih (Jurnal Riset Daerah, 2025)
This best practice research aims to examine students’ critical thinking skills through the implementation of the Viral Issue Based Learning model combined with the Focus Group Discussion method in economics lessons on the topic of inflation in Class XI.B of SMAN 1 Bantul, Yogyakarta. This research is a qualitative descriptive study involving 36 students as subjects. Data were collected through observation, questionnaires, and learning outcomes. To measure students’ critical thinking abilities, four indicators were used: (1) identifying problems; (2) analyzing problems; (3) solving problems; and (4) drawing conclusions.The research showed that the critical thinking skills of students in Class XI.B of SMAN 1 Bantul improved after undergoing the learning process using the Viral Issue Based Learning model with the Focus Group Discussion method. Their critical thinking ability increased from the moderate category (76.7%) to the high category (85.3%). Each critical thinking indicator also showed improvement. The ability to identify problems rose from 91.7% to 95.2%, the ability to analyze problems increased from 82.6% to 89.6%, problem-solving ability improved from 70.8% to 81.3%, and the ability to draw conclusions increased from 61.1% to 75%. Students’ learning outcomes in answering HOTS (Higher Order Thinking Skills) questions, which require critical thinking skills, also improved, with the average score increasing from 80.9 to 86.7. It can therefore be concluded that there was an improvement in students’ critical thinking skills through the application of Viral Issue Based Learning combined with the Focus Group Discussion method in Class XI.B of SMAN 1 Bantul